Pembingkaian Rasisme Dan Identitas Etnis Dalam Film “The Hate U Give” Sebagai Bentuk Perlawanan Melalui Media Populer - Erika, Putri; Sonni, Alem Febri; Muhammad Akbar (Elite : English and Literature Journal, 2025)
This research examines how The Hate U Give portrays racism and racial identity as forms of resistance against injustice. Using a qualitative method, the study analyses the film’s narrative through its visual elements, characters, dialogues, and symbolism, applying Robert Entman’s framing theory and Dominiq Strinati’s popular culture theory within the context of resistance. The findings show that the filmmakers strongly present the struggles of the Black community, using clear and powerful imagery to evoke empathy and raise audience awareness. The main character, Starr Carter, represents the collective experiences of Black individuals in confronting acts of racism. This study highlights the crucial role of popular film in shaping public consciousness about race and identity issues by framing a narrative of resistance that stimulates collective awareness of racism. The study also finds that the film’s visual and symbolic representations play a vital role in conveying critical messages about structural injustice. It further demonstrates how popular media can function as a site of ideological struggle. Overall, this research provides insight into how film, as a cultural text, can construct discourses of resistance and enable the formation of more inclusive and transformative social consciousness. The findings show that film not only depicts social reality but also has the capacity to influence public opinion and strengthen social solidarity.